Answer
The constant of variation is
k = 27
We can then write the inverse variation equation by substituting the value of k
y = (k/x)
y = (27/x)
Step-by-step explanation
We are told that y varies inversely as x, which can be written as
y ∝ (1/x)
Introducing the constant of variation, k, we have
y ∝ (1/x)
y = k(1/x)
y = (k/x)
We can then solve for k knowing that
y = 3 when x = 9
y = (k/x)
3 = (k/9)
We can rewrite this as
(k/9) = 3
Multiply both sides by 9
(k/9) × 9 = 3 × 9
k = 27
Hope this Helps!!!